CLINICAL AND PATHOGENETIC VARIANTS OF MALADAPTATION TO PREGNANCY AT EARLY STAGES OF GESTATION - I. S. Lipatov; Yu. V. Tuzikov; O. A. Kutuzova; A. V. Prikhod'ko; N. A. Frolova; S. A. Ryabova (Акушерство, гинекология и репродукция, 2017)
The aim of the study was to classify clinical and pathogenetic variants of early toxicosis in pregnant women based on clinical manifestations and markers of gestational maladaptation.Materials and methods. In the first trimester of gestation, 45 healthy pregnant women and 160 pregnant women with early toxicosis of varying severity were examined. The comparison group was comprised of 33 healthy non-pregnant women. In addition to the clinical symptoms, a number of laboratory markers were measured. Those included the indicators of inflammation, energy balance of the reproductive system, endometrial functional activity, vascular endothelial and hemostatic disorders, as well as blood biochemistry. Results. The obtained data were used to quantify the factors of "physiological damage" and "mechanisms of gestational adaptation" in the case of physiological gestation, and to identify the embryo-placental dysfunction as a major mechanism of maladaptation in the early stages of pregnancy. The results allowed us to propose four clinical and pathogenetic variants of early toxicosis.Conclusion. The suggested selective approach to clinical and laboratory manifestations of early toxicosis based on its classification and severity, makes it possible to rationalize the therapy, predict the risk of severe and late obstetrical complications, and reduce the risk of adverse perinatal outcomes.